Study on Competition Characteristics of a Land Cover Crop Arachis pintoito Growth of Cocoa - John Bako Baon; Yunita Anugrina; Cahya Ismayadi (Indonesian Coffee and Cocoa Research Institute, 2006)
The existence of ground cover crop, such as Arachis pintoiin cocoa farm may enhance physical, chemistry and biological fertility of soil. Nevertheless, the presence of those cover crops potentially increase the competition with main crop in various means. The primary objective of this study was to investigate kinds of competition raised when cocoa plants cultivated with ground cover crop of A. pintoi. This study consisted of three experiments. The first experiment aimed to study possible allelopatic competition using root exudates solution of A. Pintoi as well as Leucaena leucocephalaand Adenanthera microsperma as check for being used for watering cocoa plants. The second experiment aimed to study the competition between A. pintoiand cocoa plants in field condition with 1) cover crop fully overlay ground surrounding cocoa basal trunk, 2) no cover crop overlay ground surrounding cocoa basal trunk in a distance of 40 cm in diameter, and 3) no cover crop as check. Third experiment aimed to study the competition between A. pintoiand cocoa plants in limited growth medium (pot), using 10 cm stolon shoots each 4, 2 and 0 shoots per pot. Results showed that A. Pintoidid not produce alleopatic exudates to restrict cocoa growth. Population of A. Pintoi had negative effect on cocoa plant growth in the field by reducing fresh trunk weight and dry root weight, even greater negative effect found in cocoa plant grown in limited growth medium by also reducing dry leaf and trunk weight and leaf area. Key words: Theobroma cacao, Arachis pintoi, allelopathy, competition, denantheramicrosperma, Leucaena leucocephala